How Koo beat Coke: building a brand narrative versus traditional advertising - Irwin, Ronald (Department of Communication Science, University of the Free State, 2015)
The 2011 annual top brand survey, conducted by Sunday Times in South Africa, provided a representative cross-section of 33 brands from various categories in the general consumer space, and 13 in the business landscape. The overall favourite brand in South Africa in that year was Koo, owned by Tiger Brands in South Africa. This brand, which has a relatively small advertising budget, was a surprise winner in the category that had been dominated by brands such as Coca‑Cola and KFC. These brands spent far more on advertising to a lesser effect than Koo, a significantly smaller company. Koo had in fact spent R12 million on advertising versus Coke’s R193 million, yet Koo’s final ranking was the highest of all brands surveyed. The brand’s relatively simple outdoor marketing as well as the Mama Koo Radio Hour, a daily radio show featuring the various dishes homemakers can cook using Koo products, helped bring the brand to all South Africans and eclipsed its larger American-based rivals. This article considers the Koo example as illustrative of the power of simple, traditional advertising in the multi-modal context.
Keywords: Sunday Times; Koo; Coca‑Cola; Advertising; Marketing; Brands; Multi-modal context; Top brand survey